(untitled) (International Journal of Applied Research in Management and Economics, 2024)
The concept of sustainability has gained attention in academia, business, and policy, driven by concerns about environmental degradation, social inequities, and economic imbalances. This study analyzes scientific research and the evolution of sustainability, focusing on the automotive industry in management, business, and economics. Conducted from May to August 2023, a bibliometric analysis explores global trends, revealing diverse contributions. It emphasizes the need to enhance industry sustainability, particularly in the automotive sector, a significant contributor to global emissions responsible for 10% of the greenhouse gas emissions. Regulations for achieving net-zero emissions extend from production to vehicle usage. Despite substantial volume of sustainability-related publications between 1900-2023, a comprehensive understanding of sustainability management practices, especially in specific industries, is underdeveloped indicating a gap between existing research and the practical implementation of sustainable practices, especially within industries such as automotive.